Bibliometrics, reference enhanced databases and research evaluation - Tahira, Muzammil; Alias, Rose Alinda; Bakri, Aryati (2012)
This study presents the panoramic view of the described issues related to coverage, services and bibliometrics for Research Evaluation (RE) purposes by three reference enhanced databases. The researchers’ viewpoint is based on the relevant literature and data accessed from most preferred citation sources: Web of Science, Scopus and Google Scholar.The study seeks the worldview challenges, highlights and theorizes the core issues for those regions and disciplines that have more challenges and fewer opportunities in getting publishing, citing and cited by. It discusses the new insights and directs the stakeholders to explore other possible sources, metrics and evaluation techniques for RE.